Influence of Ag nanoparticles on state of the art MnO2 nanorods performance as an electrocatalyst for lithium air batteries. (1st February 2018) - Awan, Zahoor; Ghouri, Zafar Khan; Hashmi, Saud
Abstract: The need for an alternative and efficient electrocatalyst to replace Pt-based noble materials is a goal of prime importance in Li– air battery technology. In this work, novel silver nanoparticles-incorporated MnO2 nanorods as an air electrode bifunctional catalyst have been synthesized by a simple polyol method. The physical characteristics of the thus prepared materials are analyzed by X-ray diffraction (XRD), SEM, and Brunauer–Emmett–Teller (BET) techniques. These analyses confirmed the successful synthesis of 20 to 25 nm-sized different weight % Ag nanoparticles incorporated on α-MnO2 nanorods. Linear sweeping voltammetric results of AgMnO2 showed improved ORR performance as compared to α- MnO2 nanorods in terms of the onset potential, half wave potential and limiting current. The addition of catalysts has significantly increased the discharge capacity and overall performance of the cells. The first discharge curve of 5 wt% Ag MnO2 sample reached a maximum capacity of 3500 mAhg-1 at 2.0 V with a current density of 0.1 mA cm −2 with a plateau between 2.7 and 2.6 V. Long term stability of increasing weight percentage of Ag nanoparticles on MnO2 samples is increased. Highlights: Ag @ MnO2 nanorods have been synthesized by simple polyol method. The percentage of Ag nanoparticle has been optimized. 5 wt% Ag@MnO2 nanorods reached a maximum capacity of 3500 mAhg −1 at 2.0 V. Ag@MnO2 nanorods presents perfect cycling stability over 40 cycles.